2013
DOI: 10.1016/j.socscimed.2013.09.018
|View full text |Cite
|
Sign up to set email alerts
|

“Differently normal” and “normally different”: Negotiations of female embodiment in women's accounts of ‘atypical’ sex development

Abstract: AcknowledgementsI would like to express my deepest gratitude to the 23 interviewees who shared with me their stories about their lives. I would also like to thank the doctors, bloggers and patient organizations that helped me recruit the interviewees. KeywordsNormality, negotiation, diagnosis, sexed embodiment, atypical sex development, qualitative analysis, young women, Sweden Research highlights There is limited knowledge about facing atypical sex development as a young woman. The article explores how such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Some participants considered amenorrhoea and not having to use pills to prevent unwanted pregnancy in a positive sense, describing it as nice and unique to be out of the burden of menstruation (Guntram, ):
“You know, I in some way I kind of feel it's pretty nice not having a period… I think it's kind of a relief, in that sense. Eee not having all that and not having to be on the pill and that yeah that's really nice!
…”
Section: Resultsmentioning
confidence: 99%
“…Some participants considered amenorrhoea and not having to use pills to prevent unwanted pregnancy in a positive sense, describing it as nice and unique to be out of the burden of menstruation (Guntram, ):
“You know, I in some way I kind of feel it's pretty nice not having a period… I think it's kind of a relief, in that sense. Eee not having all that and not having to be on the pill and that yeah that's really nice!
…”
Section: Resultsmentioning
confidence: 99%
“…FG10) that most people are different in one way or another, suggesting it is "normal to be different" (also evident in e.g., Guntram, 2013). These findings highlight that whilst medical guidelines suggest that surgery is justified when specific criteria are met, what is understood as difference, and whether difference implies a problem, is socially constructed and negotiable (a concern also expressed by e.g., Kessler, 1998).…”
Section: Dealing With Differencementioning
confidence: 93%
“…Others prefer early surgery and do not regret the intervention (Fagerholm et al, 2011). One study found that intersex individuals constructed narratives that normalized their difference by either minimizing it or emphasizing variation among others, and situating their own difference as part of a constellation of sex variation (Guntram, 2013). In this way, they reinforce, resist, and reshape the two-sex imperative, thereby also contributing to the debate surrounding the (de)medicalization of intersex.…”
Section: The Case Of Intersexmentioning
confidence: 99%